Development and preliminary pilot evaluation of a brief tablet computer intervention to motivate tobacco quitline use among smokers in substance use treatment. (11th August 2017) - Brown, Richard A.; Hecht, Jacki; Bloom, Erika L.; Minami, Haruka; Kahler, Christopher W.; Abrantes, Ana M.; Dubreuil, Mary E.; Gordon, Alan; Price, Lawrence H.; Ondersma, Steven J.
Abstract : Background and Objectives: The majority of individuals in substance use disorder (SUD) treatment also smoke cigarettes; yet, the availability of smoking cessation services in SUD treatment remains limited. In this study, we developed and piloted a brief intervention for smokers in SUD treatment intended to motivate engagement in tobacco quitline treatment (TIME‐TQ). Methods: First, we interviewed 19 smokers in SUD treatment to inform the development of TIME‐TQ (Phase 1). Second, we delivered a prototype TIME‐TQ to 16 smokers in the same SUD treatment program and followed them for 3 months post‐discharge (Phase 2). Results: Feedback from Phase 1 participants was used to refine response choices and video segments included in the prototype TIME‐TQ. Phase 2 participants rated TIME‐TQ high on relevance, interest, respectfulness, and helpfulness. Additionally, they reported significant increases in readiness to quit and perceived importance of quitting after receiving TIME‐TQ. A total of 8 of the 16 accepted a quitline referral, and 8 of 13 reached for follow‐up (four referral acceptors, four decliners) reported efforts to quit or reduce smoking during the follow‐up period. However, only three received quitline counseling and none achieved a sustained period of abstinence. Conclusions and Scientific Significance: Our results suggest that TIME‐TQ activated these patients to quit smoking, but our referral method (standard fax referral) was unsuccessful in helping participants fully engage in quitline treatment or achieving a period of abstinence. Scientific Significance: We are now conducting an RCT to evaluate TIME‐TQ with a revised referral procedure intended to increase treatment engagement and, ultimately, abstinence rates. (Am J Addict 2017;26:587–594)